Pengaruh Anggaran Pemerintahan Desa Dibidang Kesehatan Dan Pendidikan Terhadap Kesejahteraan Pendududk Desa Koendrafo - Anima Buulolo (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2023)
This study aims to determine the influence of the village government budget in the health sector on the welfare of the population, to determine the influence of the village government budget in the education sector on the welfare of the population, to determine the village government budget in the health and education sector simultaneously influences the welfare of the population. Data analysis is used in This study uses regression analysis. The results of this study indicate that the influence of government expenditure on health and education has a significant effect on the welfare of the population (simultaneous).